Managing Curriculum Innovation to Enhance Education Quality at MA Tahfidz Al-Qur’an Banyuwangi - Syarifudin, Khabib (Journal of Basic Education Research, 2025)
Purpose of the study: This study examines the management of curriculum innovation aimed at improving the quality of education at MA Tahfidz Al-Qur'an Sumbermulyo Pesanggaran Banyuwangi, focusing on the integration of the national curriculum with tahfidz programs. Methodology: A qualitative approach with a case study design was employed. Data were collected through in-depth interviews, participatory observation, and documentation. Analysis followed the Miles and Huberman interactive model, encompassing data reduction, data display, and conclusion drawing. Main Findings: The study revealed two key findings: (1) successful integration of the national curriculum with the tahfidz program, resulting in a balanced model of academic and spiritual education; and (2) the influence of transformative leadership in fostering a culture of innovation and collaboration. These elements significantly enhance educational quality and institutional identity. Novelty/Originality: This research introduces a distinctive model of curriculum integration that aligns national education standards with tahfidz programs in Islamic schools. It proposes a practical framework demonstrating how visionary leadership and contextual innovation can synergistically advance both academic excellence and spiritual character development